2002
DOI: 10.1016/s1044-0305(01)00356-7
|View full text |Cite
|
Sign up to set email alerts
|

Solution composition and thermal denaturation for the production of single-stranded PCR amplicons: Piperidine-induced destabilization of the DNA duplex?

Abstract: Strategies to produce single-stranded PCR amplicons for detection by electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI-FTICR-MS) were investigated using modified electrospray solutions and by thermally denaturing the duplex structures with a resistively heated electrospray ionization source. A synthetic 20-mer oligonucleotide annealed to its complementary strand was used as a model system for initial experiments. Electrospray solutions were altered by varying the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…It has been demonstrated that solution conditions, thermal denaturaturation effects, and the intrinsic hydrophobicity of the individual strands of the PCR product can significantly influence spectral characteristics (Mangrum, Flora, & Muddiman, 2002;Null, Nepomuceno, & Muddiman, 2003). Null and co-workers demonstrated that the ESI-FTICR signal intensity of oligonucleotides containing an alkyl modification on the 5 0 -terminus is enhanced relative to their non-modified counterparts.…”
Section: Genotyping and Forensics Applicationsmentioning
confidence: 99%
“…It has been demonstrated that solution conditions, thermal denaturaturation effects, and the intrinsic hydrophobicity of the individual strands of the PCR product can significantly influence spectral characteristics (Mangrum, Flora, & Muddiman, 2002;Null, Nepomuceno, & Muddiman, 2003). Null and co-workers demonstrated that the ESI-FTICR signal intensity of oligonucleotides containing an alkyl modification on the 5 0 -terminus is enhanced relative to their non-modified counterparts.…”
Section: Genotyping and Forensics Applicationsmentioning
confidence: 99%
“…The heated electrospray source also denatured the unmodified SNP 22 and SNP 22 containing 7-deaza guanine (data not shown). The ability of the newly fashioned heated electrospray source to denature amplicons containing 7-deaza analogs is a salient result, especially since the previous heated electrospray source [7] was unable to denature these species (unpublished observations).…”
Section: Heated Electrospray Sourcementioning
confidence: 99%
“…Originally, our laboratory designed a heated electrospray source in an attempt to denature duplex DNA [7]. Herein, we describe a completely redesigned source that is more stable, allowing for broader applications.…”
mentioning
confidence: 99%
“…Internal calibration for PCR amplicons derived from simple and compound STRs Electrospray solution compositions were adjusted to promote the detection of only single-stranded PCR amplicons for all oligonucleotide spectra [45]. Figure 2 shows ESI-Q-ToF mass spectra obtained for the single-stranded HUMTH01 PCR amplicons generated from a synthetic template ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting average mass error for the 35.6 kDa molecule confirmed that the individual is homozygous for allele 18 rather than allele 18'. It has also been shown that single-stranded PCR amplicons can be generated by increasing the aqueous content of the ESI solution [45].…”
Section: Jason W Flora · Allison P Null · David C Muddimanmentioning
confidence: 99%